The Relationship between Industrial Environment and Financial Performance (Evidences Small and Medium Enterprises in East Java Region, Indonesia - Ismanu, Sidik; Kusmintarti, Anik; ., . (International Journal of Engineering and Technology, 2018)
This study examines the efect of industrial environment towards the financial performance of Small and Medium Enterprises (SMEs). The object of research is SMEs of handmade batik in east java region, Indonesia. Handmade batik as a fabric product with original Indonesian creations, pure making process using hand drawing on cloth. SMEs of handmade batik in east java region-Indonesia can not be removed with industrial environment. Industrial environment as a business factor outside the company that can cause opportunities or threats that affect the company's competitive advantage. Industrial environment as an independent variable with variable dimension consisting of power of new competitors, bargaining power of supplier, bargaining power of buyer and intensity of competition. Financial performance is a form of performance achieved by companies that are determined from financial information as a fundamental factor. Data collection method was done through questionnaire, consisting of 84 respondents. Hypothesis test is done by multiple regression processed. Research findings, industrial environment have a positive and significant influence on financial performance. Dynamics of the industrial environment as an external factor of the company, will make business activities have a better prospect.Â Â
Keywords: industrial environment; financial performance; small and medium enterprices (SMEs); Handmade batik.